A General Palladium‐Catalyzed Carbonylative Synthesis of Chromenones from Salicylic Aldehydes and Benzyl Chlorides. Issue 37 (12th August 2013) - Wu, Xiao‐Feng; Wu, Lipeng; Jackstell, Ralf; Neumann, Helfried; Beller, Matthias
<x xml:space="preserve">Abstract</x> Cute CO! An interesting and straightforward procedure for the carbonylative synthesis of chromenones from readily available salicylic aldehydes and benzyl chlorides has been developed (see scheme; DPPP=1, 3‐bis(diphenylphosphino)propane). In the presence of a palladium catalyst, various coumarins were produced in good to excellent yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>